UPAYA WORLD COSPLAY SUMMIT EXECUTIVE COMMITTEE MENINGKATKAN CITRA POSITIF JEPANG MELALUI EVENT BUDAYA POPULER COSPLAY - Akhimuddin, M. Faiz (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research discusses the efforts made by the World Cosplay Summit Executive Committee to improve Japan's positive image through the Cosplay popular culture even. Japan’s image as a country was negatively impacted after World War II. Popular culture is one of the tools that an international actor can use to increase their support or positive image internationally. One example of popular culture that is of interest to the international community is cosplay. The World Cosplay Summit is the largest cosplay popular culture event held in Japan. This research uses a qualitative case study method using secondary data sources obtained through literature study. This research uses the theory of public diplomacy. The result of this research is the implementation of public diplomacy in an effort to implement the World Cosplay Summit, namely through the use of popular culture and providing information, influencing, and engaging the public both at Japan and abroad in the implementation of cosplay popular culture events. Keywords: Country images, Cosplay Popular culture, Public diplomacy,